KONTRIBUSI DAYAH DALAM PENGEMBANGAN INTELEKTUAL DI ACEH - Muhammad Hasbi Amiruddin (Kalam: Jurnal Agama dan Sosial Humaniora, 2017)
If we face the world in this modern era there is no other way for human beings except to see the purpose of education that many people want to achieve in order to be a faithful and devout, then a dayah is an institution that does not do it. But following the changing times with technological developments, dayah requires the addition of its curriculum. It’s time to offer the skills sciences, as well as the formulation of national education goals. Moreover, with the influence of globalization, whoever the scientists must have the breadth of knowledge so as not to get lost with the traps of people who do not want Islam is seen as a good religion